Oak Mills, Atchison County - Grape, Hannah (Kansas State University, The Chapman Center for Rural Studies, 2013)
This report contains historical journal references, history obtained through genealogical archives, investigative local folklore, maps spanning several decades, and photos and references from the author's personal knowledge and affiliation with the town of Oak Mills, located in Walnut Township, Atchison County.
Hannah Grape, “Oak Mills, Atchison County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/123.
Keywords: Kanza; Osage; Oak Mills; Atchison County; Cow Island; John Waddle